Therapeutic effects of different regimens for induction therapy in elderly patients more than 50 years old with newly diagnosed acute myeloid leukaemia - Liu, Junmei; Zhong, Liang; Yao, Juanjuan; Zhong, Pengqiang; Yuan, Zhen; Liu, Dongdong; Li, Lianwen; Liu, Lu; Zhao, Yi; Yao, Shifei; Chen, Min; Liu, Beizhong (Translational Cancer Research, 2018)
Background: Acute myeloid leukaemia (AML) is a highly heterogeneous disease that commonly occurs in elderly cohorts. To date, there is still no standard induction therapy for elderly AML patients, and they experience low complete remission rates and short survival time. Methods: We retrospectively analysed the clinical data of 86 AML patients aged ≥50 years admitted at the First Affiliated Hospital of Chongqing Medical University and the Second Affiliated Hospital of Chongqing Medical University. The patients were divided into three groups, idarubicin plus cytarabine (IA) group; decitabine, cytarabine, aclarubicin, and granulocyte stimulating factor (D-CAG) group; and daunorubicin plus cytarabine (DA) group. Patients’ adverse reactions, complete remission (CR) rates, overall response (OR) rates, and long-term survival conditions were compared. Results: The CR rates of the IA group, D-CAG group, and DA group were 47.4%, 54.3%, and 42.9%, respectively (P=0.659), and the OR rates were 52.6%, 71.4%, and 71.4%, respectively (P=0.311). The median survival time of the IA group was 12.47 months, while that of the D-CAG group was 28.6 months (P=0.180). All of the above results had no statistical difference. However, the D-CAG group had lower incidence of haematological adverse reactions, fever, and gastrointestinal response of grade II or above than the DA Group and IA group. Conclusions: This study showed that IA regimen, D-CAG regimen and DA regimen have similar therapeutic effect on patients aged ≥50 years with newly diagnosed AML while D-CAG regimen shows fewer adverse reactions. Age and bone marrow blasts at initial diagnosis are risk factors for prognostic.